Water transport by Na(+)-coupled cotransporters of glucose (SGLT1) and of iodide (NIS). The dependence of substrate size studied at high resolution - Zeuthen*, Thomas (Blackwell Science Inc, 2006)
The relation between substrate and water transport was studied in Na(+)-coupled cotransporters of glucose (SGLT1) and of iodide (NIS) expressed in Xenopus oocytes. The water transport was monitored from changes in oocyte volume at a resolution of 20 pl, more than one order of magnitude better than previous investigations. The rate of cotransport was monitored as the clamp current obtained from two-electrode voltage clamp. The high resolution data demonstrated a fixed ratio between the turn-over of the cotransporter and the rate of water transport. This applied to experiments in which the rate of cotransport was changed by isosmotic application of substrate, by rapid changes in clamp voltage, or by poisoning. Transport of larger substrates gave rise to less water transport. For the rabbit SGLT1, 378 ± 20 (n = 18 oocytes) water molecules were cotransported along with the 2 Na(+) ions and the glucose-analogue α-MDG (MW 194); using the larger sugar arbutin (MW 272) this number was reduced by a factor of at least 0.86 ± 0.03 (15). For the human SGLT1 the respective numbers were 234 ± 12 (18) and 0.85 ± 0.8 (7). For NIS, 253 ± 16 (12) water molecules were cotransported for each 2 Na(+) and 1 thiocyanate (SCN(−), MW 58), with I(−) as anion (MW 127) only 162 ± 11 (19) water molecules were cotransported. The effect of substrate size suggests a molecular mechanism for water cotransport and is opposite to what would be expected from unstirred layer effects. Data were analysed by a model which combined cotransport and osmosis at the membrane with diffusion in the cytoplasm. The combination of high resolution measurements and precise modelling showed that water transport across the membrane can be explained by cotransport of water in the membrane proteins and that intracellular unstirred layers effects are minute.